Integrated framework for assessing green efficiency in European union countries: A hybrid ISM-NDEA approach - Afarin Rezaei; Hoda Moradi; Alireza Anvari (International Journal of Research in Industrial Engineering, 2025)
Environmental sustainability has become a primary concern for businesses and policymakers aiming to balance economic growth with ecological preservation. This urgency is driven by the increasing pressures of climate change, resource depletion, and heightened societal expectations for sustainable practices. Recognizing the need for a method to assess environmental and economic efficiency, this study introduces an innovative hybrid approach that combines Interpretive Structural Modeling (ISM) with Network Data Envelopment Analysis (NDEA), offering a refined framework for measuring green efficiency that addresses both environmental and economic dimensions. This methodology leverages expert insights to pinpoint and organize key variables affecting green efficiency, employing ISM to construct a comprehensive model. The ISM-structured model informs the selection of a suitable DEA variant (either simple or network) and elucidates the role of each variable as an input, intermediate process, or output measure. Subsequently, green efficiency values are calculated using the DEA model identified by ISM. This approach is then applied to calculate the green efficiency of  European Union (EU) countries, providing a benchmark for measuring green efficiency across the EU. Our analysis uncovers significant findings that highlight disparities in green efficiency among EU members, revealing areas for policy improvement and resource allocation. The insights gleaned from this study have implications for stakeholders seeking to enhance their operational sustainability, providing a roadmap for better-informed and more effective policy and business strategies aimed at fostering sustainable development.